Planning support systems for sustainable urban development / Stan Geertman, Fred Toppen, John Stillwell - Geertman, Stan
This book collects a selection of the best articles presented at the CUPUM (Computers in Urban Planning and Urban Management) conference, held in the second week of July 2013 in Utrecht, the Netherlands. The articles included were selected by external reviewers using a double blind process.